Social, Religious, and Economic Interaction Spaces as a Community Representational Space - Ima Rahmawati Sushanti; Purwanita Setijanti; Dewi Septanti (Journal of Islamic Architecture, 2024)
Place identity relates to the meaning and importance of a place to its residents and users and how these meanings contribute to an individual's self-conceptualization. The order of Islamic values in a place as spirit can move the community to practice them daily to create identity, which will easily observed in public spaces. Islamic values in religious traditions are suspected to underlie ongoing social and economic activities in this space. This research aims to determine the identity of public spaces in urban settlements based on Islamic values on a city scale. The research paradigm is naturalistic, with case studies and qualitative descriptive research methods. The research location is the corridor of Sekarbela district, Mataram city, where most people are Muslim. Data collection involves interviews, observation, and documentation of activities. The analysis used behavior setting and spatial and micro activities techniques. Research results show that the representation of public space is practicing Islamic values through local traditions in spider networks centered on the mosque. The community agrees and works together to practice Islamic values for social togetherness, economic independence, and environmental comfort so that local traditions can continue and become the color of public spaces.